Preparation of PVDF/TiO2 nanofibers with enhanced piezoelectric properties for geophone applications. (1st July 2019) - Zhu, Jianfeng; Sun, Hongshuai; Xu, Yang; Liu, Tao; Hou, Tianyuan; Liu, Lishuang; Li, Yongchao; Lin, Tingting; Xin, Yi
Abstract: For deep seismic detection, a geophone with high sensitivity to low frequency seismic signals is needed. In this work, polyvinylidene fluoride (PVDF)/TiO2 nanofibers with enhanced piezoelectric properties have been electrospun and applied on the geophone for increasing the sensitivity of sensing unit. The nanofibers were characterized by scanning electron microscopy and transmission electron microscopy, x-ray diffraction spectra (XRD) and fourier transform infrared spectroscopy (FTIR). According to (XRD) and (FTIR), electrospinning method and doping of titanium dioxide particles promote the orderly arrangement of molecules and increase the β polymorph. Moreover, a sensing unit with spiral cantilever beam for further improving the sensitivity and low frequency response was fabricated and the spiral cantilever beam was optimized by simulation. Afterwards, a geophone with the sensing unit was assembled and tested under absolute calibration system. The results show that sensitivity of the sensing unit itself without circuit can be up to 144 mV m −1 s −2 . Such a strong raw signal will meet the needs of geophone with high signal-to-noise ratio for deep exploration. Furthermore, its low frequency cut-off frequency is 3 Hz, which are superior to the conventional geophone based on piezoelectric ceramic.